Pensión gracia : marco normativo, jurisprudencial y doctrinal en Colombia (2015)
This work we access to the legal framework, jurisprudence and doctrine grace of pension recognized for teachers of Colombian teachers. The same can be different legal glimpse change to be submitted along the Colombian history. The purpose of this research is to clarify the different interpretations presented for the case, revealing the principles and / or requirements that the law brings in order not to generate legal uncertainty concerning the case that concerns us herein. This in order to guarantee a right and a teacher appreciation of Colombia.